Possibilities of ultrasonographic determination of the distribution of purulent-necrotic lesions of the anorectal and urogenital areas in acute paraproctitis complicated by sepsis. - Kanikovskyi, O. Ye.; Osadchyi, A. V.; Mosondz, V. V.; Kotsiura, O. A. (Medicni Perspektivi, 2018)
An urgent problem of the present day is an acute purulent infection, a significant part of which are patients with acute purulent pathology of the pararectal area. The aim of the work is to determine the ultrasonographic criteria of purulent-necrotic lesion in acute paraproctitis. Endorectal sonography makes it possible to determine the nature of pathological changes in cell spaces with a high probability and to conduct differential diagnostics of acute paraproctitis with diseases of neighboring organs. The use of ultrasonographic system control in clinical practice in the purulent-necrotic lesion of the anorectal and urogenital zone significantly improved the results of treatment. Intraoperative use of ultrasonographic examination allowed less traumatic and adequate drainage of the pelvic space in purulent-necrotic lesions.